On the distribution of the species of the genus Hebius Thompson, 1913 (Squamata: Natricidae) in northern Thailand, including the description of a new species and a discussion on snake diversity of this region - Hauser, Sjon; Smits, Ton; David, Patrick (Zootaxa, 2022)
We examined and identified preserved specimens, skins, and photographs from a collection of 83 snakes from northern Thailand presenting the characters of the genus Hebius Thompson, 1913. They belong to at least six different taxa divided into five species including a new one described here, namely H. bitaeniatus (Wall, 1925), H. deschauenseei (Taylor, 1934), H. igneus David, Vogel, Nguyen, Orlov, Pauwels, Teynié & Ziegler, 2021, Hebius khasiensis (Boulenger, 1890), and a series of specimens with strong similarities to H. khasiensis that are here preliminary identified as “Hebius cf. khasiensis”. Furthermore, we obtained a series of 21 different specimens in the most western strip of the region that we could not refer to any presently known species. We refer these specimens to a new species that we describe here. For each of these taxa, we provide the list of localities and specify the geographic range in northern Thailand. Lastly, we also discuss the diversity of the snake fauna of northern Thailand.